Surgical Management of Vertical Class III Malocclusion with Severe Skeletal Openbite Using Minimum Pre-surgical Orthodontics - A Case Report - Husain, Seerab; Khan, Nayeemullah; Parameswaran, Anantanarayanan; Nagi, Manini; Parameswaran, Ratna (Annals of maxillofacial surgery, 2025)
Abstract Rationale and Patient Concerns: A 19-year-old male patient presented with a dentoalveolar Class III malocclusion on a Class III skeletal base with facial asymmetry, increased facial proportions, complicated by anterior open bite of 6.2 mm, unilateral posterior crossbite with Index of Orthognathic Functional Treatment Need score of 5.4. Diagnosis and Treatment: The patient's maxillary arch was bonded initially and 4 months post alignment, pre-surgical intraoral scanning and full skull computed tomography were obtained and subjected to virtual surgical planning (NemoFAB Version 22, Nemotec, Madrid, Spain). Counterclockwise rotational bilateral sagittal split osteotomy setback and genioplasty was performed to close the open bite and correct the Class III skeletal discrepancy with the aid of intermaxillary fixation screws placed in the midline of upper and lower maxillary and mandibular arches for heavy elastic engagement post-surgery. Outcome: Facial balance was restored, profile was improved, ideal overjet and overbite established. Take-away Lessons: This approach combines the benefits of conventional three-phase surgery and surgery first orthognathic approach by meticulous planning of the intended transitional malocclusion to achieve a stable occlusion. Longer follow-ups in future studies can be investigated.